Study on Distribution Characteristics and Displacement Mechanism of Microscopic Residual Oil in Heterogeneous Low Permeability Reservoirs. (21st October 2019) - Fang, Yujia; Yang, Erlong; Cui, Xiaona
Abstract : In order to explore the development methods suitable for heterogeneous low permeability reservoirs and study the distribution characteristics of residual oil, photoetched glass and artificial core models with three permeability ratios of 1, 6, and 9 were prepared in this research. Three displacement schemes including polymeric surfactant flooding, polymeric surfactant with binary flooding, and binary flooding were designed at the same expenses to obtain the displacement mechanism of various residual oil saturations. The results show that the best displacement efficiency can be achieved by polymeric surfactant flooding, followed by polymeric surfactant with binary flooding, and binary flooding for the models with the same permeability ratio. Binary flooding mainly activates cluster and oil drop residual oils, polymeric surfactant with binary flooding mainly activates cluster, oil film, and column residual oils, whereas polymeric surfactant flooding mainly activates cluster, oil drop, and column residual oils. In addition, with the increase of the model permeability ratio, the recovery ratio of water flooding decreases, whereas the enhanced oil recovery and the variations in residual oil saturation gradually increase after carrying out different displacement measures. The viscoelastic and shearing effects of the polymeric surfactant flooding system can better displace the residual oil, assisting in the further development of heterogeneous low permeability reservoirs.